Birthing Fathers : The Transformation of Men in American Rites of Birth - Reed, Richard K., 1954- (Book collections on Project MUSE., 2005)
In the past two decades, men have gone from being excluded from the delivery room to being admitted, then invited, and, finally, expected to participate actively in the birth of their children. No longer mere observers, fathers attend baby showers, go to birthing classes, and share in the intimate, everyday details of their partners' pregnancies. In this unique study, Richard Reed draws on the feminist critique of professionalized medical birthing to argue that the clinical nature of medical intervention distances fathers from child delivery. He explores men's roles in childbirth and the ways in which birth transforms a man's identity and his relations with his partner, his new baby, and society. In other societies, birth is recognized as an important rite of passage for fathers. Yet, in American culture, despite the fact that fathers are admitted into delivery rooms, little attention is given to their transition to fatherhood. The book concludes with an exploration of what men's roles in childbirth tell us about gender and American society. Reed suggests that it is no coincidence that men's participation in the birthing process developed in parallel to changing definitions of fatherhood more broadly. Over the past twenty years, it has become expected that fathers, in addition to being strong and dependable, will be empathetic and nurturing. Well-researched, candidly written, and enriched with personal accounts of over fifty men from all parts of the world, this book is as much about the birth of fathers as it is about fathers in birth.